Peran Konsultan Pendidikan untuk Meningkatkan Kompetensi Guru - Muhammad Zia- ulHaq; Natriani Syam; Romansyah Sahabuddin; Muhammad Irfan (Universitas Muhammadiyah Gresik, 2024)
Pedagogical and professional competencies are crucial for creating effective and meaningful learning. In the era of educational transformation, educational consultants provide strategic solutions to support teacher competency development through needs-based training, intensive mentoring, and data-driven evaluations. This article aims to explore the role of educational consultants in enhancing teachers' pedagogical and professional competencies, based on recent literature from the last five years. The findings indicate that educational consultants' involvement improves teachers' classroom management, curriculum comprehension, and implementation of innovative teaching methods. It is recommended that schools, governments, and educational consultants work together to ensure sustainable teacher competency development..